METODE PEMBELAJARAN SEJARAH BERBASIS SISWA DENGAN PENDEKATAN KONSTRUKTIVIS DI TINGKAT PENDIDIKAN MENENGAH - Junita, Reja; Agustina, Bela; Afriyanto, Rian; Susilo, Agus (Journal of Language Teaching Lingustics and Literature, 2024)
This study aims to analyze the method of student-based history learning with a constructivist approach at the secondary education level. Learning is the process of interaction between students and teachers and learning resources in a learning environment, constructivist learning is the process by which students construct their own knowledge. Constructivist history learning refers to history learning activities that are based on the constructivism paradigm. Constructivism in the realm of education views that students autonomously build or construct knowledge and intelligence through interaction with the physical and social world. Constructivism should naturally inspire students to provide honest responses and engage in conversations about the material they are studying. The research method used by the researcher is a literature approach by collecting sources in articles using literature reviews in books and scientific articles.